2007
DOI: 10.1300/j005v33n01_08
|View full text |Cite
|
Sign up to set email alerts
|

HIV Service Provision for People with Severe Mental Illness in Outpatient Mental Health Care Settings in New York

Abstract: People with severe mental illness evidence significantly higher rates of HIV infection than the general population in the United States. Frequently, the only access to health care for this population is through their outpatient mental health care providers. In order to determine how these providers were dealing with the increased risk of HIV infection among this group, a survey of all licensed and certified outpatient mental health care centers in New York State was conducted. The data were compared to a simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Implementing routine HIV testing in mental health settings (where screening is low due to: limited availability of on-site testing, clinician discomfort providing risk reduction counseling and administering HIV tests, and provider concerns that HIV testing may detract from the delivery of mental health care) and targeting outreach and testing campaigns towards those with mental illness may help improve testing rates in this at-risk population. [37][38][39][40] In addition, mentally ill persons who use illicit drugs should be screened for HIV when initiating treatment for substance abuse. 41 Lastly, linkage to and retention in HIV care are necessary, given poorer HIV outcomes for persons with versus those without psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing routine HIV testing in mental health settings (where screening is low due to: limited availability of on-site testing, clinician discomfort providing risk reduction counseling and administering HIV tests, and provider concerns that HIV testing may detract from the delivery of mental health care) and targeting outreach and testing campaigns towards those with mental illness may help improve testing rates in this at-risk population. [37][38][39][40] In addition, mentally ill persons who use illicit drugs should be screened for HIV when initiating treatment for substance abuse. 41 Lastly, linkage to and retention in HIV care are necessary, given poorer HIV outcomes for persons with versus those without psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[13,16] In a survey of psychiatric hospitals and outpatient mental health centres, the majority of staff reported that they only encouraged a few patients to get tested. [17] Joska et al [18] report that state psychiatrists in SA's Western Cape Province do not test routinely for HIV infection (14.6% of patients with serious mental illness were tested in 2006), largely because of ethical constraints.…”
Section: Increasing Hiv Testing Rates In the Mentally Ill Through Thementioning
confidence: 99%
“…[8] Ideally, mental health clinicians can provide pre-and post-test counselling that is tailored for individuals with a mental illness, addressing patients' barriers to testing and allaying concerns about testing, confidentiality and stigma. [17] Mental health settings are also ideal because patients located here avoid the need for additional transportation or appointments. [17] HIV testing could be recommended during consultation, together with all other relevant tests.…”
Section: Increasing Hiv Testing Rates In the Mentally Ill Through Thementioning
confidence: 99%
See 1 more Smart Citation
“…First, most providers offer none of these services to clients, despite being their major point of access to health care. In New York, where prevalence is high and HIV services are mandated, less than half of the psychiatric providers routinely do risk assessment, and only 16% offer blood testing for HIV (8,9). Mental health providers appear to be reluctant to offer core services for the following reasons: limited financial resources; reluctance to inquire about risk behaviors; reluctance to promote testing for infection; lack of knowledge about blood-borne infections; inadequate skills and confidence in dealing with positive test results; inability to help clients access appropriate medical care (10).…”
mentioning
confidence: 99%